LRMP Associates With Immune Infiltrates and Acts as a Prognostic Biomarker in Lung Adenocarcinoma - Jin, Xin; Chen, Liwei; Zhou, Ning; Ni, Hong; Zu, Lingling; He, Jinling; Yang, Lingqi; Zhu, Yifan; Sun, Xiaoyue; Li, Xiaojiang; Xu, Song (Frontiers in Molecular Biosciences, 2021)
Background: Lymphoid-restricted membrane protein (LRMP) is an endoplasmic reticulum-associated protein that is expressed in a developmentally regulated manner in both B and T cell lineages. However, the role of LRMP inthe growth, prognosis and immune infiltration in lung adenocarcinoma (LUAD) remains unclear. Method: The expression levels of LRMP mRNA in tumor and normal tissues were analyzed using Tumor Immune Estimation Resource 2.0 (TIMER 2.0) and Gene Expression Profiling Interactive Analysis 2 (GEPIA 2). LRMP protein expression was examined using the Human Protein Atlas. In vitro experiments, including qRT-PCR、Western blot and immunohistochemistry staining were also performed to investigate LRMP expression.GEPIA2 and Kaplan-Meier plotter databases were used to analyze the clinical prognostic significance of LRMP.To further confirm the underlying function of LRMP, the data were analyzed using gene set enrichment analysis.Moreover, we also constructed plasmids to overexpress LRMP and explored the effect of LRMP in A549 cell line.Additionally, Tumor Immune single-cell Hub was used to investigate the distribution of LRMP in the LUAD immune microenvironment; TIMER and CIBERSORT were used to investigate the relationships among LRMP, LRMP co-expressed genes, and tumor-infiltrating immune cells; Finally, the correlations between LRMP and immune checkpoints were analyzed using TIMER 2.0. Results: The expression of LRMP was significantly lower in LUAD tissues and cell lines. High LRMP expression is associated with a better prognosis in patients with LUAD. In vitro experimental studies demonstrated that overexpression of LRMP could decrease the proliferation, migration and invasion in A549 cells, and downregulated multiple oncogenic signaling pathways, including p-STAT3, p-PI3K-p-AKT, p-MEK and EMT pathways.GSEA results showed that immuno-related and cell adhesion pathways were enriched in samples with high LRMP expression.LRMP and its co-expressed genes were positively correlated with various tumor-infiltrating immune cells and their markers. Additionally, LRMP positively correlated with immune checkpoints. Conclusions: Our data suggest thatLRMP may act as a tumor suppressor geneand indicates a better prognosis. Moreover, LRMP is associated with immune infiltrates which may be involved in immunotherapy response in LUAD. Further studies are needed to validate these findings.